A Comparative Study of Psychological Adjustment between Female Students Participating and Not Participating in Sports Activities at the University of Samarra - Younus, Ali Ayoob (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
The present study was set to determine what differences exist in the psychological adjustment of female students who participate in sports activities with those who do not participate at the University of Samarra. The research acquires its significance by an advanced level gap which exists due to an insufficiency of laborious field studies on the preventive and therapeutic effects through sports among female students inside Iraqi universities. This is exactly at a time when several cultural and institutional challenges are impeding their participation. The net sample came out, finally, as (94) students for the practicing group that includes those from the College of Physical Education and Sports Sciences while, for the non-practicing group, there were students from the Department of Civil Engineering. The researcher adopted the Psychological Adjustment Scale developed by Hana (1970) in her study and used an independent sample t-test for analyzing data. Results presented here mean that practicing students had better psychological adjustment at a statistically significant level than non-practicing students (mean = 105.08, mean = 83.03). Regular physical practice reduced biological stress indicators and increased the secretion of positive neurotransmitters; thus, practicing sports raises self-efficacy, self-esteem, and mental toughness as one discovers a very suitable means to control emotions and organize stress. This results from team sports giving high social support and also a state of belongingness which will boost the social and psychological adjustment of students on all fronts. This leads to increasing the general mental health of an individual student through the regular physical activities that help in adapting to challenging academic situations among Iraqi university students.